Surface-carbonized NiFe prussian blue composite electrode and preparation and application thereof

Through the NiFe Prussian Blue composite electrode with surface carbonization, the problems of high cost and limited resources of precious metal catalysts are solved, and high electrocatalytic oxygen evolution reaction and oxygen reduction reaction are achieved, with good stability and high hydrogen peroxide generation efficiency, suitable for electrolysis Application of water and electricity synthesis of hydrogen peroxide.

CN119177466APending Publication Date: 2024-12-24SOUTH CHINA UNIV OF TECH
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411190094.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-28
Publication Date
2024-12-24

AI Technical Summary

Technical Problem

Due to the high cost and limited resource reserves in the electrolytic reaction, precious metal catalysts are restricted by their large-scale use in the electrolytic water process, especially in the complex four-electron transfer process of the anode and the slow reaction kinetics, which makes the energy utilization rate low.

Method used

Using surface carbonized NiFe Prussian blue composite electrode, a high-active and good conductivity electrode is formed by growing a catalyst on a conductive substrate and salt encapsulating and partial carbonization treatment, combined with desalination and carbon etching treatment, and is used for electrocatalytic analysis. Oxygen reaction and oxygen reduction reaction.

Benefits of technology

It realizes efficient catalytic oxygen evolution reaction and oxygen reduction reaction at low overpotentials, with good stability and high hydrogen peroxide generation efficiency, and is suitable for the application of electrolytic water and electrosynthesis hydrogen peroxide, reducing production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119177466A_ABST
    Figure CN119177466A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of electrochemistry, and discloses a surface-carbonized NiFe Prussian blue composite electrode as well as preparation and application thereof. The preparation method comprises the following steps: 1) synthesizing a Prussian-blue-like catalyst on a conductive substrate in situ; 2) carrying out confinement heat treatment on the conductive substrate with the Prussian blue-like catalyst, so that the conductive substrate retains a Prussian blue-like structure and obtains a partial carbonization effect at the same time; and 3) carrying out desalting treatment on the catalyst subjected to confinement heat treatment, and then carrying out non-confinement heat treatment to obtain the Prussian blue-like composite electrode subjected to carbon etching. The method is simple and low in cost, and the prepared electrode has good electrocatalytic activity, shows good catalytic activity and stability in electrocatalytic oxygen evolution reaction, has the advantages of high hydrogen peroxide selectivity, high activity and the like in the hydrogen peroxide electrosynthesis process, and is suitable for industrial production. The method has a good application prospect in the aspect of on-site electrosynthesis of H2O2 at normal temperature and normal pressure. The catalyst can be used for electrolyzing water and electrosynthesizing H2O2.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of electrochemical catalysis, and in particular to a surface carbonized NiFe-based Prussian blue composite electrode and preparation and application thereof. Background Art

[0002] As a non-renewable energy, fossil energy not only has limited reserves, but also easily causes environmental pollution during use and mining. Therefore, it is necessary to develop renewable resources that can replace fossil energy.

[0003] Among many renewable energy sources, hydrogen energy is considered the cleanest energy, and the main method of obtaining hydrogen energy is to obtain hydrogen through water electrolysis. In the water electrolysis reaction, oxygen evolution reaction (OER) and hydrogen evolution reaction (HER) are the key processes to achieve this reaction.

[0004] Both processes involve the generation of gas, whose large reaction energy barriers lead to excessively high overpotentials and low energy utilization.

[0005] At present, the main catalyst materials used for water electrolysis reactions are precious metal materials.

[0006] However, the shortage of precious metal reserves and high prices restrict their large-scale application in industry. The oxygen evolution reaction (OER) is an electrochemical reaction that occurs at the anode in the water electrolysis process. Its complex four-electron transfer process and slow reaction kinetics have become the main problems restricting large-scale water electrolysis to produce hydrogen. The main means to solve this problem is to use highly active electrocatalysts to effectively reduce the overpotential in the oxygen absorption reaction process, thereby improving the energy conversion efficiency.

[0007] Currently, Ir-based and Ru-based noble metal catalysts have shown high activity in the electrocatalytic oxygen evolution reaction, but the high cost and limited resource reserves of noble metal-based catalysts have greatly restricted the widespread application of these materials in the commercial field.

[0008] Therefore, it is of great significance to find a transition metal-based electrocatalyst that is abundant, inexpensive and has high oxygen evolution activity. Summary of the invention

[0009] The purpose of the present invention is to overcome the above-mentioned shortcomings and deficiencies of the prior art and to provide a surface carbonized NiFe-based Prussian blue composite electrode and its preparation and application.

[0010] The composite electrode prepared by the present invention has good OER and ORR catalytic performance and stability, and has good 2e - ORR selectivity.

[0011] The preparation process of the invention is simple and effective, and the entire synthesis process is green and controllable, which is conducive to the mass production of the electrode.

[0012] The present invention is achieved through the following technical solutions:

[0013] A method for preparing a NiFe-based Prussian blue composite electrode comprises the following steps:

[0014] Step 1) preparing a Prussian blue-like catalyst on a conductive substrate nickel foam;

[0015] Step 2) salt encapsulation treatment is performed on the nickel foam grown with the Prussian blue-like catalyst, followed by partial carbonization treatment at different temperatures;

[0016] Step 3) Desalting the partially carbonized composite electrode, and then drying it, and then performing carbon etching on the dried composite electrode.

[0017] In the above step 1), the growth condition of the Prussian blue-like catalyst is 25° C. and the growth time is 18 h.

[0018] In the above step 1), the solution for growing the Prussian blue-like catalyst is a mixed solution of potassium ferrocyanide and trisodium citrate, wherein the concentration of potassium ferrocyanide in the mixed solution is 0.03M; and the concentration of trisodium citrate in the mixed solution is 0.02M.

[0019] In the above step 2), the salt encapsulation treatment is to immerse the composite electrode in a saturated potassium chloride solution and perform freeze-drying treatment at -60°C to finally obtain a composite electrode with potassium chloride coated on the surface.

[0020] In the above step 2), the partial carbonization treatment at different temperatures is achieved by heat treatment at different temperatures in an argon environment. Specifically, the salt-encapsulated composite electrode is heat treated at 30°C, 300°C, 350°C, 400°C, 450°C, 500°C, and 800°C for 1 hour, respectively, with an argon atmosphere and a flow rate of 60 mL / min.

[0021] In the above step 3), the desalination treatment is to immerse the partially carbonized composite electrode in deionized water, then perform ultrasonic treatment for 1 minute, and then dry it.

[0022] In the above step 3), the carbon etching treatment is to perform heat treatment on the composite electrode at different temperatures in an air environment, the heat treatment temperature is 400° C., and the heat treatment time is 1 hour.

[0023] In the above step 1), the Prussian blue-like catalyst is obtained by in-situ growth in a mixed solution of potassium ferrocyanide and trisodium citrate.

[0024] In the above steps 1-3, the obtained electrodes are rinsed with water and anhydrous ethanol in sequence and dried naturally.

[0025] The NiFe-based Prussian blue composite electrode of the present invention can electrocatalyze oxygen evolution reaction and 2e - Oxygen reduction produces hydrogen peroxide.

[0026] Experiments show that the NiFe-based Prussian blue composite electrode has good electrocatalytic performance in oxygen evolution reaction and hydrogen peroxide generation. When catalyzing the oxygen evolution reaction, the current density is j = 10 mA cm -2 When the overpotential η is 198mV, the highest hydrogen peroxide Faraday efficiency is about 95.5% when catalyzing the oxygen reduction reaction. Moreover, the electrode has good stability and can produce H2O2 stably for 10 hours, with a H2O2 output of 280.3μmol.

[0027] The surface carbonized NiFe-type Prussian blue composite electrode obtained by the preparation method of the present invention is used in electrocatalytic oxygen evolution reaction and electrocatalytic synthesis of hydrogen peroxide (H2O2).

[0028] Compared with the prior art, the present invention has the following advantages and effects:

[0029] (1) The present invention provides a surface carbonized NiFe-based Prussian blue catalyst composite electrode through a simple solution synthesis method. The entire synthesis process is green, controllable, and easy to prepare.

[0030] (2) The present invention utilizes a salt encapsulation method to partially carbonize the original Prussian blue-like catalyst, so that its surface is coated with a layer of carbon, thereby retaining the high catalytic activity centers of the Prussian blue-like catalyst and improving the conductivity of the material.

[0031] (3) The present invention adopts carbon etching treatment to reduce the thickness of the carbon layer on the surface of the material through heat treatment in air, thereby exposing more active sites.

[0032] (4) The present invention uses a solution synthesis method to grow a Prussian blue-like catalyst in situ on a conductive substrate, thereby improving the conductivity of the electrode.

[0033] (5) The present invention prepares a self-supporting electrode with transition metal as active center and high performance 2-electron electrosynthesis of hydrogen peroxide, which is expected to realize on-site electrosynthesis of hydrogen peroxide for wastewater treatment and sterilization and disinfection. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 SEM images of the Prussian blue-like composite electrodes (NiFe-PBA-SE-NSE / NF) prepared in Examples 1, 2, and 3.

[0035] Figure 2 XRD patterns of the Prussian blue-like composite electrodes (NiFe-PBA-SE-NSE / NF) prepared in Examples 1, 2, and 3.

[0036] Figure 3 LSV diagram, overpotential, Tafel curve and impedance diagram of the oxygen evolution reaction catalyzed by the Prussian blue-like composite electrode (NiFe-PBA-SE-NSE / NF) prepared in Example 1.

[0037] Figure 4 The Faraday efficiency and H2O2 yield of the Prussian blue-like composite electrode (NiFe-PBA-SE-NSE / NF) prepared in Example 2 for catalytic ORR in an H-type electrolytic cell.

[0038] Figure 5 Faradaic efficiency and H2O2 yield of the Prussian blue-like composite electrode (NiFe-PBA-SE-NSE / NF) prepared in Example 3 for catalyzing ORR in a flow cell.

[0039] Figure 6 This is a stability test of the catalytic ORR prepared in Example 3 at 0.3V.

[0040] Figure 7 The LSV diagram, overpotential and Tafel curve diagram of the oxygen evolution reaction catalyzed by NiFe-PBA prepared in Example 4. DETAILED DESCRIPTION

[0041] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the following is further described in detail with reference to the accompanying drawings and specific embodiments, but the embodiments of the present invention are not limited thereto.

[0042] In the examples, the experimental methods used are conventional methods unless otherwise specified, and the materials, reagents, etc. used are all commercially available unless otherwise specified.

[0043] Embodiment 1:

[0044] A method for preparing a surface carbonized NiFe-based Prussian blue composite electrode comprises the following steps:

[0045] (1) First, the nickel foam was pretreated by cutting the nickel foam into 2×1 cm size, placing it in anhydrous ethanol for ultrasonic treatment for 30 minutes; then taking it out and placing it in 3M concentrated hydrochloric acid for ultrasonic treatment for 30 minutes. After taking it out, it was thoroughly washed with deionized water, and finally left to stand in a wet environment for 2 days to form a nickel oxide layer on the surface of the nickel foam.

[0046] (2) Next, nickel foam with in-situ growth of NiFe-PBA was prepared by preparing a 0.02M potassium ferrocyanide solution and adding an appropriate amount of trisodium citrate. The pretreated nickel foam sheet was placed in the solution and allowed to stand for 24 hours to obtain NiFe-PBA / NF.

[0047] (3) The nickel foam sheet on which NiFe-PBA was grown in situ was placed in a saturated potassium chloride solution and then frozen with liquid nitrogen for salt encapsulation. The frozen sample was placed in a freeze dryer for drying.

[0048] (4) The dried material was placed in a porcelain boat and then heated under an argon gas flow rate of 50 mL min -1 The confined heat treatment was carried out at 350°C, 375°C, 400°C, 425°C and 450°C for 1 h to obtain NiFe-PBA-SE / NF-x (x is the temperature of the confined heat treatment).

[0049] (5) The heat-treated material was washed with water to remove the surface potassium chloride and then further oxidized and carbon-etched. The material was kept in air at 400°C for 1 hour to obtain NiFe-PBA-SE-NSE / NF-x (x is the temperature of the confined heat treatment).

[0050] See also Figure 1 , Figure 1 These are SEM images of the Prussian blue-like composite electrodes prepared in Examples 1, 2, and 3.

[0051] See also Figure 2 , Figure 2 These are the XRD patterns of the Prussian blue-like composite electrode in Example 1 and Examples 2 and 3.

[0052] The Prussian blue-like composite electrode prepared in this example was used as the anode for oxygen evolution reaction for electrocatalytic water decomposition, with a 1*1 cm Pt sheet as the counter electrode and an Ag / AgCl electrode as the reference electrode. -1 Argon was introduced at a flow rate of 100 ℃ for 15 minutes, and then the electrochemical performance was tested using a three-electrode system.

[0053] See also Figure 3 , Figure 3 The LSV diagram, overpotential, Tafel curve and impedance diagram of the oxygen evolution reaction catalyzed by the Prussian blue-like composite electrode in Example 1.

[0054] The Prussian blue composite electrode prepared in Example 1 was used as the working electrode to test the CV and LSV curves, and the tafel and impedance curves were calculated based on the LSV curves. The test results showed that the NiFe-PBA-SE-NSE / NF-x after confinement-non-confinement heat treatment had the best electrocatalytic OER performance when the current density was j=10mAcm -2 , the overpotential η = 198mV.

[0055] Embodiment 2:

[0056] A surface carbonized Prussian blue-like composite electrode, the preparation method of this embodiment is the same as that of embodiment 1, except that the catalyzed reaction is an oxygen reduction reaction.

[0057] Figure 4 LSV diagram, H2O2 Faraday efficiency, and H2O2 yield of the Prussian blue-like composite electrode (NiFe-PBA-SE-NSE / NF) prepared in Example 2 catalyzing ORR in an H-type electrolytic cell;

[0058] The Prussian blue composite electrode prepared in this example was used as the cathode of the oxygen reduction reaction for electrocatalytic synthesis of H2O2. An H-type electrolytic cell was used as the generator, a 1*1 cm Pt sheet was used as the counter electrode, an Ag / AgCl electrode was used as the reference electrode, and the electrolyte was 0.1 M KOH. Before the test, 40 mL min -1 Oxygen was introduced at a flow rate of 100 μg / min for 15 minutes to saturate the electrolyte, and then tested using a three-electrode system. The electrolysis was performed at a potential of 0.3 V (relative to the standard hydrogen electrode) for 1 hour, and the H2O2 concentration was determined by the conventional cerium sulfate titration method. The selectivity of NiFe-PBA-SE-NSE / NF-400 at a potential of 0.3 V can reach 82.35%, and the H2O2 yield of 1 hour electrolysis is 7.4 mg h -1 g cat -1 .

[0059] Embodiment 3:

[0060] A surface carbonized Prussian blue-like composite electrode, the preparation method of this embodiment is the same as that of embodiments 1 and 2, except that a flow cell system is used to simultaneously catalyze oxygen evolution reaction and oxygen reduction reaction.

[0061] Figure 5 Faradaic efficiency and H2O2 yield of the Prussian blue-like composite electrode (NiFe-PBA-SE-NSE / NF) prepared in Example 3 for ORR catalysis in a flow cell;

[0062] The Prussian blue-like composite electrode prepared in this example was used as the cathode of the oxygen reduction reaction and the anode of the oxygen evolution reaction. A flow cell system was used as a generator, an Ag / AgCl electrode was used as a reference electrode, and the electrolyte was 0.1 M KOH. Before the test, the electrolyte was heated at 40 mL min -1 Oxygen was introduced at a flow rate of 100 μg / min for 15 minutes to saturate the electrolyte, followed by a three-electrode system test. Electrolysis was performed at potentials of 0.5 V, 0.4 V, and 0.3 V (relative to the standard hydrogen electrode) for 1 hour, and the H2O2 concentration was determined by the conventional cerium sulfate titration method. The selectivity of Pd / Ni@ZnO-3NTAs at a potential of 0.3 V can reach 98.5%, and the H2O2 yield of 1 hour of electrolysis is between 20 and 30 mg h -1 g cat -1 between.

[0063] The stability test was carried out within 12 hours, and the Faraday efficiency FE during the process was >80%; the average hourly yield Y = 29.91gh -1 g cat -1 , indicating that its stability is good.

[0064] Embodiment 4:

[0065] A surface carbonized NiFe-based Prussian blue composite electrode, the preparation method of which comprises the following steps:

[0066] (1) Prepare 50 mL of 0.02 M nickel chloride and potassium ferrocyanide solution respectively, and add 0.5 g of trisodium citrate to the potassium ferrocyanide solution. Then mix the two solutions, let stand for 24 hours, and centrifuge three times with deionized water. The obtained precipitate is dried in an oven set at 60°C;

[0067] (2) Grind the dried sample into powder, take an appropriate amount of powder into a porcelain boat, and then flow it under an argon gas flow rate of 50 mL min -1 The heat treatment was carried out under the following conditions. The heat treatment was carried out at 300°C, 350°C, 400°C, 450°C, 500°C and 800°C for 1 hour. The final product was represented by NiFe-PBA-x (x is the heat treatment temperature).

[0068] (3) NiFe-PBA-x is evenly spread on a conductive substrate to obtain a composite electrode.

[0069] See also Figure 7 , Figure 7 The LSV diagram, overpotential, and Tafel curve diagram of the oxygen evolution reaction catalyzed by NiFe-PBA prepared in Example 4;

[0070] The Prussian blue composite electrode prepared in Example 4 was used as the working electrode to test the CV and LSV curves, and the Tafel curve was calculated based on the LSV curve. The test results showed that NiFe-PBA-400 had the best electrocatalytic OER performance. -2 , the overpotential η = 219mV.

[0071] As described above, the method of the present invention is simple and low in cost. The prepared electrode has good electrocatalytic activity and exhibits good catalytic activity and stability in the electrocatalytic oxygen evolution reaction. At the same time, it has the advantages of high hydrogen peroxide selectivity and high activity in the process of electrosynthesizing hydrogen peroxide, and has good application prospects in the field electrosynthesis of H2O2 at normal temperature and pressure. The catalyst of the present invention can be used for electrolysis of water and electrosynthesis of H2O2.

[0072] The implementation methods of the present invention are not limited to the above-mentioned embodiments, and any other changes, modifications, substitutions, combinations, and simplifications made without departing from the spirit and principles of the present invention shall be equivalent replacement methods and shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a surface carbonized NiFe-based Prussian blue composite electrode, characterized in that: The following steps are involved: Step 1: preparing NiFe-based Prussian blue crystals on a conductive substrate; Step 2: salt encapsulation treatment is performed on the conductive substrate on which the NiFe-type Prussian blue crystals are grown, and a partial carbonization heat treatment is performed; after the partial carbonization heat treatment, excess salt is washed away, and then a carbon etching treatment is performed in the air.

2. The method for preparing the surface carbonized NiFe-based Prussian blue composite electrode according to claim 1, characterized in that: The conductive substrate in step 1 is nickel foam.

3. The method for preparing the surface carbonized NiFe-based Prussian blue composite electrode according to claim 1, characterized in that: The NiFe-based Prussian blue crystals described in step 1 are synthesized by nickel foam in a mixed solution of potassium ferrocyanide and trisodium citrate; wherein the concentration of potassium ferrocyanide in the mixed solution is 0.02M, and the concentration of trisodium citrate in the mixed solution is 0.01M.

4. The method for preparing the surface carbonized NiFe-based Prussian blue composite electrode according to claim 1, characterized in that: During the salt encapsulation treatment in step 2, the conductive substrate on which the NiFe-type Prussian blue crystals are grown is added to a saturated potassium chloride solution, frozen using liquid nitrogen, and then freeze-dried; The partial carbonization heat treatment in step 2 is to carry out heat preservation treatment on the composite electrode material under argon gas conditions; the specific conditions are: argon gas flow rate of 60 mL / min, and heat preservation temperature of 400°C.

5. The method for preparing the surface carbonized NiFe-based Prussian blue composite electrode according to claim 1, characterized in that: In step 2, the excess salt is washed away by using deionized water; the carbon etching treatment refers to heat preservation treatment of the electrode material in an air environment.

6. The method for preparing the surface carbonized NiFe-based Prussian blue composite electrode according to claim 5, characterized in that: The electrode material should be fully dried before carbon etching; the carbon etching temperature is 400°C.

7. The method for preparing the surface carbonized NiFe-based Prussian blue composite electrode according to claim 5, characterized in that: The partial carbonization heat treatment in step 2 is carried out in a tube furnace; after partial carbonization and carbon etching, the electrode material needs to be washed with deionized water and dried.

8. The method for preparing the surface carbonized NiFe-based Prussian blue composite electrode according to claim 2, characterized in that: When synthesizing Prussian blue-like crystals, the nickel foam is firstly acid-washed and washed with water, and then allowed to stand at room temperature for 2 days, and then added to the mixed solution and allowed to stand for 1 day; The solution used in the pickling process is 1M hydrochloric acid; the static environment is a dark and dry environment.

9. A surface carbonized NiFe-based Prussian blue composite electrode obtained by the preparation method according to any one of claims 1 to 8.

10. Use of the surface carbonized NiFe-based Prussian blue composite electrode according to claim 8 in electrocatalytic oxygen evolution reaction and electrocatalytic synthesis of hydrogen peroxide (H2O2).

Citation Information

Cited By

  • Preparation method and application of CuFe Prussian blue analogue cubic array electrocatalyst

    CN119824458A

  • Post-treatment method of carbon-supported platinum-based catalyst

    CN120033264A